Proceso de atención de enfermería en paciente masculino de 60 años de edad con insuficiencia renal crónica estadio 4. - Zamora López, María De Los Ángeles (2020)
Renal failure is the inability of the kidneys to excrete waste products from the body, concentrate urine and conserve electrolytes, manifesting clinically: nutritional disorders, metabolism abnormalities and homeostasis. Chronic renal failure consists of a progressive and irreversible destruction of the nephrons of both kidneys. The main causes that lead to chronic kidney failure are: Diabetes, hypertension, primary glomerulopathies. In the development of this clinical case, I will present the nursing care and attention that should be taken before this type of patient, providing knowledge about the treatment of a 60-year-old patient with a diagnosis of stage IV chronic renal failure, who enters the area IESS Babahoyo Hospital emergency department due to loss of mobility in lower extremities, I have intense pain, after consultation with the nephrology service, in which a rigorous plan of nutritional care was established with periodic reviews every 3 months.